Type I interferon signaling before hematopoietic stem cell transplantation lowers donor T cell activation via reduced allogenicity of recipient cells - Fischer, Julius C.; Bscheider, Michael; Goetter, Sascha; Orberg, Erik Thiele; Combs, Stephanie E.; Bassermann, Florian; Heidegger, Simon; Haas, Tobias; Poeck, Hendrik (Scientific Reports, 2019)
Recent studies highlight immunoregulatory functions of type I interferons (IFN-I) during the pathogenesis of graft-versus-host disease (GVHD) after allogeneic hematopoietic stem cell transplantation (allo-HSCT). We demonstrated that selective activation of IFN-I pathways including RIG-I/MAVS and cGAS/STING prior to allo-HSCT conditioning therapy can ameliorate the course of GVHD. However, direct effects of IFN-Is on immune cells remain ill characterized. We applied RIG-I agonists (3pRNA) to stimulate IFN-I production in murine models of conditioning therapy with total body irradiation (TBI) and GVHD. Using IFN-I receptor-deficient donor T cells and hematopoietic cells, we found that endogenous and RIG-I-induced IFN-Is do not reduce GVHD by acting on these cell types. However, 3pRNA applied before conditioning therapy reduced the ability of CD11c+ recipient cells to stimulate proliferation and interferon gamma expression of allogeneic T cells. Consistently, RIG-I activation before TBI reduced the proliferation of transplanted allogeneic T-cells. The reduced allogenicity of CD11c+ recipient cells was dependent on IFN-I signaling. Notably, this immunosuppressive function of DCs was restricted to a scenario where tissue damage occurs. Our findings uncover a context (damage by TBI) and IFN-I dependent modulation of T cells by DCs and extend the understanding about the cellular targets of IFN-I during allo-HSCT and GVHD.
CRIS-Team Scopus Importer:2023-03-08